Ionic Liquids as a Non-conventional Catalyst for the Synthesis of N-heterocycles - Singh, Pradeep P.; Kanodia, Saraswati; Ambika (Mini-Reviews in Organic Chemistry, 2024)
Ionic liquids (ILs) have emerged as one of the potential alternates of organic solvents in chemistry. Nitrogen-containing heterocyclic compounds are the important structural motifs of some bioactive compounds. A variety of ILs, such as first-generation, second-generation, and thirdgeneration ILs have been used in the synthesis of various types of nitrogen-containing heterocyclic compounds, such as aziridine, indole, pyrrazole, imidazole, oxazole, thiazole, triazole, pyridine, pyrimidine, quinolones, benzodiazapiene and their derivatives. Due to their unique chemical and physical properties, ILs can act as both solvent and catalyst and have contributed towards high efficiency, improved yield and recyclability for the synthesis of heterocyclic skeleton. In this review, the application of ILs in the synthesis of different nitrogen-containing heterocyclic compounds has been discussed.
Keywords: green solvents